Rapid and Sensitive Detection of Bacteria by Gas Chromatography - Mitruka, B. M. (1968)
A gas chromatograph fitted with electron capture and flame ionization detectors was employed for the rapid detection of bacteria by analysis for their metabolic products. The presence of Proteus vulgaris, Streptococcus faecalis, S. liquefaciens, Escherichia coli B, Bacillus cereus, and B. popilliae was detected in 2 to 4 hr in media inoculated with less than 10(4) cells per ml, whereas a 7- to 12-hr growth period was required for the detection of products formed in cultures of Serratia marcescens, Aerobacter aerogenes, E. coli K-12, Staphylococcus aureus, and Salmonella typhimurium. Metabolites elaborated by the equivalent of less than a single cell of B. cereus, S. faecalis, P. vulgaris, or E. coli B were sensed by the electron capture detector. The flame ionization detector was generally not as sensitive. Volatile metabolites were identified, and their concentrations were determined.